RETRACTED: Exosomal MicroRNA-221-3p Confers Adriamycin Resistance in Breast Cancer Cells by Targeting PIK3R1 - Pan, Xiaoping; Hong, Xiaolv; Lai, Jinguo; Cheng, Lu; Cheng, Yandong; Yao, Mingmei; Wang, Rong; Hu, Na (Frontiers in Oncology, 2020)
Drug resistance in breast cancer (BC) cells continues to be a stern obstacle hindering BC treatment. Adriamycin (ADR) is a frequently employed chemotherapy agent used to treat BC. Exosomal transfer of microRNAs (miRNAs) has been reported to enhance the drug-resistance of BC cells. Herein, we first sought to elucidate the possible role of the exosomal transfer of miR-221-3p in the drug resistance of MCF-7 cells to ADR. Differentially expressed genes (DEGs) were initially screened through microarray analysis in BC drug resistance-related datasets. Next, the expression of miR-221-3p and phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) was quantified in ADR-resistant MCF-7 (MCF-7/ADR) and ADR-sensitive MCF-7 (MCF-7/S) cell lines, after which exosomes were separated and identified in each cell line. Target relationship between miR-221-3p and PIK3R1 was validated by dual-luciferase reporter assay. Next, the expression of miR-221-3p and PIK3R1 was altered to clarify their effects on the resistance of MCF-7 cells to ADR in vitro and in vivo. PIK3R1 was identified as a BC drug resistance-related DEG, with the regulatory miR-221-3p subsequently obtained. Moreover, the MCF-7/ADR cells exhibited low expression of PIK3R1 and high expression of miR-221-3p. Notably, PIK3R1 was identified as a target gene of miR-221-3p. The overexpression of miR-221-3p in MCF-7/ADR cell-derived exosomes promoted ADR resistance in MCF-7/S cells via the PI3K/AKT signaling pathway. The in vitro results were reproducible in in vivo assays. Taken together, drug-resistant BC cell-derived exosomal miR-221-3p can promote the resistance of BC cells to ADR by targeting PIK3R1 via the PI3K/AKT signaling pathway in vitro and in vivo. These findings provide encouraging insight and provide perspective for further investigation into the BC drug resistance mechanism.